The effect of the William Exercise on reducing lower back pain in patients at FPM Sunny Surakarta - Shella Dhika Rahmawati; Aulia Ayu Kusuma W; Lulu'ah Feby Purwanti (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2023)
In everyday life, work is important for every individual to fulfill life's needs, every job definitely requires movement activities in the body. Lifting heavy weights and sitting for too long are examples of activities that humans often do. If this activity is done repeatedly, it will trigger health problems, one of which is lower back pain. Low back pain is a symptom caused by various abnormalities, whether known or unknown, low back pain is one of the many problems that are often encountered in society. As many as 84% of people will experience lower back pain problems. This pain is located between the thoracic area 12 to the gluteus (Cahya et al., 2016).